Keratin: dissolution, extraction and biomedical application - Shavandi, Amin (2017)
Keratinous materials such as wool, feathers and hooves are tough unique biological co-products that usually have high sulfur and protein contents. A high cystine content (7–13%) differentiates keratins from other structural proteins, such as collagen and elastin. Dissolution and extraction of keratin is a difficult process compared to other natural polymers, such as chitosan, starch, collagen, and a large-scale use of keratin depends on employing a relatively fast, cost-effective and time efficient extraction method. Keratin has some inherent ability to facilitate cell adhesion, proliferation, and regeneration of the tissue, therefore keratin biomaterials can provide a biocompatible matrix for regrowth and regeneration of the defective tissue. Additionally, due to its amino acid constituents, keratin can be tailored and finely tuned to meet the exact requirement of degradation, drug release or incorporation of different hydrophobic or hydrophilic tails. This review discusses the various methods available for the dissolution and extraction of keratin with emphasis on their advantages and limitations. The impacts of various methods and chemicals used on the structure and the properties of keratin are discussed with the aim of highlighting options available toward commercial keratin production. This review also reports the properties of various keratinbased biomaterials and critically examines how these materials are influenced by the keratin extraction procedure, discussing the features that make them effective as biomedical applications, as well as some of the mechanisms of action and physiological roles of keratin. Particular attention is given to the practical application of keratin biomaterials, namely addressing the advantages and limitations on the use of keratin films, 3D composite scaffolds and keratin hydrogels for tissue engineering, wound healing, hemostatic and controlled drug release.